A new phenolic glycoside from Saprosma merrillii. Issue 21 (1st November 2016) - Zhou, Xue-Ming; Zheng, Cai-Juan; Song, Xiao-Ping; Chen, Guang-Ying; Cao, Yu-Hua; Huang, A-Qian; Su, Shao-Hui; Chen, Wen-Xing; Yang, Hui
Abstract: A new phenolic glycoside derivative, saproglucoside (1 ), along with five known phenolic glycoside derivatives (2–6 ) were isolated from the stems of Saprosma merrillii . The structure of the new compound1 was determined by 1D and 2D NMR as well as by HRESIMS and hydrolysis. The inhibitory activities of all compounds against seven pathogenic bacteria and two cancer cell lines were evaluated. Abstract :